OPTIMALISASI KETERBATASAN SUMBER DAYA MANUSIA DALAM PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) PADA KANTOR PERTANAHAN KABUPATEN KEBUMEN - Widodo Widodo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2022)
Complete Systematic Land Registration (CSLR) is one of the national strategic programs of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency to accelerate land registration throughout Indonesia. The government sets a target that all land parcels in Indonesia are to be certified by 2025 through the CSLR program with the aim of ensuring legal certainty of land ownership for the people. The CLSR target in 2017 was 5 million certificates, 7 million certificates in 2018, 9 million certificates in 2019 and for 2020-2025 the target is 10-13 million certificates every year. This large target is constrained by the limited human resources available at the regional Land Offices. The purpose of this study is to analyze the strategy of optimizing the limited human resources in the implementation of the CSLR program which was carried out by the Land Office of Kebumen Regency. In this study, the strategy of optimizing human resources at the Land Office of Kebumen Regency was carried out through optimizing human resources in every stage of CSLR management carried out, including planning, organizing, directing and supervising. Optimization of human resource in the implementation of the CSLR program at the Land Office of Kebumen Regency is carried out by analyzing existing internal and external human resource problems, and finding solutions to these problems using SWOT. Efforts made in this optimization included regular monitoring and evaluation, competency mapping and employee training, improving coordination and communication, utilizing student apprentices and optimizing the performance of the CSLR village team.